Práticas cotidianas e direitos:as táticas da rede Dêbandeira pela vida dos LGBT+ em Mossoró/RN (2015-2020) - Silva, Vando Rocha da (2023)
The objective of the research was to analyze the strategies undertaken by the DêBandeira Network between the years 2015 and 2020, regarding the consolidation of LGBT+ rights in the city of Mossoró, Rio Grande do Norte. The aforementioned collective was formed in 2013, but it was in 2015 that it officially organized itself. This work sought to understand the process of formation, as well as the actions that this group has been undertaking in the fight for the rights of the LGBT+ population in Mossoró. Within this perspective, three axes of action of the Network were highlighted: justice, human rights, and public policies; education; and activism in virtual environments. In this direction, the study analyzed how these axes are articulated with local and national LGBT+, what demands are addressed by each axis, and how the Network acts upon them. As a specific objective, the study also sought to methodologically identify the paths of recent brazilian historiographical production on the history of LGBT+ movements in Brazil. Therefore, from a methodological standpoint, a combination of bibliographic analysis and field study was employed. Interviews were conducted with the founding activists of the DêBandeira Network who are still involved in the collective today. The interviews were conducted through open-ended questions, recorded, and later transcribed and analyzed based on data interpretation and bibliographic dialogue. The results indicated a strong institutional involvement of the DêBandeira Network, as its activists operate in different political groups and spaces, such as councils and political parties. Additionally, other areas of activism are also engaged, such as universities, schools, and social media. Over the years, the DêBandeira Network has sought to establish a direct dialogue with the government, despite facing numerous challenges. It was pointed out that there is a need for broader articulation with social movements and sectors of the population, aiming to exert greater pressure on government officials who show inertia in the face of the demands of the LGBT+ community in Mossoró. In theory, there is still a long way to go, but it needs to mobilize the masses towards the streets.